An Experimental Study of Game-Based Music Education of Primary School Children - (:unkn) unknown (ACAD CONFERENCES LTD, 2008)
In order to determine which method would be more successful in teaching Rythm in Music to the sixth grade 12 year old students, a state primary school (in Turkey) was chosen. An experimental study pre-test and post test method with a control group was held and was carried out with a total of 52 students 26 of whom were in the study group and 26 in the control group. In this study, it was aimed to observe how children respond in learning the two, four and eighth note values and rhythm patterns and whether they were able to identify the notes, reproduce them in beats and write down what they listen to (notation). Teaching to both groups The Element of Rhythm by means of games called Bingo, Wheel and the follow up activity of Write down What You Listen to was the main aim of this study. Researchers collected data by means of: a) a personal information form containing information about each student's background; b) an information test prepared by the researchers to evaluate the knowledge of the student about The Element of Rhythm, in Music and given before and after the experimental study; c) an observation form for each student which was filled in throughout the games played and activities done in the classroom. The duration of the study was for four weeks. The students took a pre-test at the beginning of the four-week period and a posttest at the end. According to the findings after the pre and posttests, the skills and capabilities of the 6(th) grade primary school children in recognizing, playing and writing down the note durations of quarter, half and eighth notes as well as the rhythm patterns consisting of various partitions differentiated substantially according to the teaching method used in the classroom. Furthermore, with respect to the relation to the variable of gender and the variable the financial status of the family and the variable of the parents' educational background and the variable of the parents' occupation point out to slight differences in the achievement rate of the students. Consequent to the research, it is found out that the children in the study group were far more successful than the children in the control group at every stage.
Keywords: Music education; musical games; rhythm education; classroom music education; RHYTHMIC ABILITY; PRESCHOOL-CHILDREN